A Name Change for Quercus Incana Roxb. Is Inevitable - Bahadur, K. N. (Indian Forester, 1975)
The Indian Quercus incana Roxb. (1832) is a later homonym of the American Q. incana Bartr (1791). The former, therefore, has to be renamed. A scrutiny of the synonyms mentioned in literature for this oak reveals that the names Q. lanata Sm. (1814), Q. oblongata D. Don (1825) and Q. dealbata Wall. (1831) are not tenable for one reason or another. Q. leucotrichophora A. Camus nom. Subnud. (1935), the only other alternative name available for the Indian species, is being validated and proposed here as an avowed subtitute.